Learning Styles and Difficulties of College Students in Chemistry - Montenegro, Marleo B; Cascolan, Dr Honelly Mae S (ASEAN Journal of Basic and Higher Education, 2020)
This study set out to identify the most and least dominant learning styles and difficulties in organic chemistry of the second year college students coming from the 7 campuses of Pangasinan State University namely: Asingan, Bayambang, Binmaley, Infanta, Lingayen, San Carlos, and Sta. Maria who took up organic chemistry subject during the school year 2018-2019. The instruments used were survey-questionnaires. The first questionnaire was adopted from Grasha and Reichmann learning style model Turkish Adaptation by Saritas and Sural (2010) comprised of 6 dimensions which are the learning style. These are independent, dependent, participant, avoidant, collaborative, and competent learning styles. Each dimension is composed of 10 items, in total, 60 items. Each learning styles were determined at three levels of low medium and high. The second questionnaire was made by the researchers consists of thirty-five (35) questions and the respondents would rate themselves as to their perceived level of difficulty of the performance task in organic chemistry. To statistically treat the data, frequency counts, percentages, average weighted mean, spearman rho and point biserial were employed. The most dominant learning styles of the respondents in this study were collaborative and competitive learning styles; and least dominant were independent and participant learning styles. It was understood that difficult performance tasks were from the following topics; bonding and molecular structure; functional groups overview; organic reactions and their mechanisms; stereochemistry; and alkenes, alkynes and aromatic compounds. Moreover, students who have independent, avoidant and collaborative learning styles find all the performance tasks as difficult.